2006
DOI: 10.1002/jnr.20706
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cochlear ablation on muscarinic acetylcholine receptor binding in the rat cochlear nucleus

Abstract: Cholinergic synapses in the cochlear nucleus (CN) have been reported to modulate spontaneous activity via muscarinic acetylcholine receptors. In this study, muscarinic receptor binding was measured as specific binding of 1-[N-methyl-(3)H]scopolamine in CN regions of control rats and 7 days, 1 month, and 2 months after unilateral cochlear ablation. In control rats, the strongest binding was found in granular regions, followed in order by fusiform soma, molecular, and deep layers of the dorsal cochlear nucleus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 72 publications
4
23
0
Order By: Relevance
“…As for the mechanism of the Ca 2+ transients, the decisive role of muscarinic acetylcholine receptors is indicated by the strong blocking effect of atropine documented in the present experiments as well as in earlier publications [5,6,18].…”
Section: Muscarinic Modulation Of Dcn Granule Cellssupporting
confidence: 79%
See 1 more Smart Citation
“…As for the mechanism of the Ca 2+ transients, the decisive role of muscarinic acetylcholine receptors is indicated by the strong blocking effect of atropine documented in the present experiments as well as in earlier publications [5,6,18].…”
Section: Muscarinic Modulation Of Dcn Granule Cellssupporting
confidence: 79%
“…Several data obtained under various experimental conditions point toward a facilitatory influence of cholinergic innervation at different stages of the auditory pathway. In the CN, for example, possible cholinergic excitation of the ventral part was proposed [2]; an amplifier function of cholinergic modulation in the DCN was hypothesized [18], and most recently an increased activity of the giant cells on CCh application has been reported [26]. The latter effect might be (at least partly) the consequence of the elimination of the short-term depression present at the parallel fibre-giant cell synapses.…”
Section: Muscarinic Modulation Of Dcn Granule Cellsmentioning
confidence: 99%
“…In a cochlear ablation study in rats, we found a sustained asymmetry of muscarinic receptor binding, higher on the lesion side, after surgery (Jin and Godfrey, 2006). Since increases of ChAT activity in the CN of intense-tone-exposed hamsters resemble in some respects our previous finding of increased ChAT activity in the CN of cochlear-ablated rats, we might speculate that muscarinic receptor expression in the exposed-side CN of hamster might increase relative to the opposite CN, as in rat CN after cochlear ablation.…”
Section: Effects Of Intense Tone Exposure On Chat Activitymentioning
confidence: 92%
“…However, a portion of the leucine uptake is likely used in metabolic pathways related to up-and down-regulation of neurotransmitters and their receptors, which undergo significant bilateral changes after hearing loss (e.g., Potashner et al, 1997Potashner et al, , 2000Suneja et al, 1998aSuneja et al, ,b, 2000, as well as the expression of proteins, such as calcium binding proteins (e.g., Caicedo et al, 1997;Förster and Illing, 2000), GAP-43 (Michler and Illing, 2002;Kraus and Illing, 2004) and synaptophysin (e.g., Benson et al, 1997) which are also up-and down-regulated following hearing loss. Jin and Godfrey (2006) found that CA affects muscarinic acetylcholine receptor binding in the AVCN bilaterally, where binding increases steadily from 7 days to 2 months post ablation, with a 42% increase in the contralateral AVCN. This suggests the possibility of significant modulation of activity within neurons of AVCN via intracellular G-proteins.…”
Section: Unilateral Hearing Loss Alters Protein Synthesis Bilaterallymentioning
confidence: 97%